Effect of platelet-rich plasma in treating musculoskeletal disorders in athletes - Biondo, Mattia; Di Rosa, Luigi; Tomasello, Laura; Baldassano, Sara; Borsellino, Francesca; Vasto, Sonya (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Platelet-rich plasma (PRP) is a product of significant interest in the field of regenerative medicine due to its healing, immu-nomodulatory and anti-inflammatory properties. Although its role remains debated, PRP has undeniably shown considerable potential in aiding the healing of various injuries and pathologies across multiple fields, from dermatology (e.g., hair loss, skin scars) to reproductive medicine and inflammatory diseases (e.g., osteoarthritis). The aim of this review is to summarise and describe the role of PRP in treating common musculoskeletal injuries and pathologies in athletes. This population is at higher risk for such conditions due to the physical activities they perform. However, the application of PRP in this context has not been sufficiently explored in the literature. After providing a brief overview of precision and regenerative medicine – distinct yet interconnected fields – we will examine the key characteristics of PRP and its role in treating various musculo-skeletal injuries in athletes. This review highlights the current applications of PRP, its potential for future use and its limitations.
Keywords: platelet-rich plasma; athletes; tendinopathy; athletic injuries; regenerative medicine